Nitrogen Addition Exacerbates the Negative Effects of Low Temperature Stress on Carbon and Nitrogen Metabolism in Moss - Liu, Bin-Yang; Lei, Chun-Yi; Liu, Wei-Qiu (Frontiers in plant science, 2017)
Global environmental changes are leading to an increase in localized abnormally low temperatures and increasing nitrogen (N) deposition is a phenomenon recognized worldwide. Both low temperature stress (LTS) and excess N induce oxidative stress in plants, and excess N also reduces their resistance to LTS. Mosses are primitive plants that are generally more sensitive to alterations in environmental factors than vascular species. To study the combined effects of N deposition and LTS on carbon (C) and N metabolism in moss, two moss species, subsp. , and , exposed to various concentrations of nitrate (KNO ) or ammonium (NH Cl), were treated with or without LTS. C/N metabolism indices were then monitored, both immediately after the stress and after a short recovery period (10 days). LTS decreased the photosystem II (PSII) performance index and inhibited non-cyclic photophosphorylation, ribulose-1,5-bisphosphate carboxylase, and glutamine synthetase activities, indicating damage to PSII and reductions in C/N assimilation in these mosses. LTS did not affect cyclic photophosphorylation, sucrose synthase, sucrose-phosphate synthase, and NADP-isocitrate dehydrogenase activities, suggesting a certain level of energy and C skeleton generation were maintained in the mosses to combat LTS; however, LTS inhibited the activity of glycolate oxidase. As predicted, N supply increased the sensitivity of the mosses to LTS, resulting in greater damage to PSII and a sharper decrease in C/N assimilation. After the recovery period, the performance of PSII and C/N metabolism, which were inhibited by LTS increased significantly, and were generally higher than those of control samples not exposed to LTS, suggesting overcompensation effects; however, N application reduced the extent of compensation effects. Both C and N metabolism exhibited stronger compensation effects in than in subsp. . The difference was especially pronounced after addition of N, indicating that may be more resilient to temperature and N variation, which could explain its wider distribution in the natural environment.